Challenges to achieving BMT in the treatment of AML in Brazil: Bahia University Hematology Center experience - Feistauer, Felipe; Salvino, Marco; Batista, Marianna; Crusoe, Edvan; Teixeira, Lais; Ponte, Alini; Favano, Thiago; Correia, Camilla; Noblat, Lucia de Araujo Costa Beisl (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
Introduction: Acute myeloid leukemia is a heterogeneous aggressive leukemia with a poor prognosis. The standard remission induction regimen for medically eligible patients consists of a backbone of cytarabine & anthracycline. Objective: This study assessed the efficacy and safety of cytarabine and anthracycline in a public health center in Salvador, Brazil. Methods: It is a retrospective analysis of 45 non-promyelocytic AML patients diagnosed between 2018 and 2022. Subgroups analyzed included patients having FTL3 and NPM1 mutations, leukocyte count (>10,000 or <10,000), platelets count (>20,000 or <20,000), and transplanted patients. Kaplan-Meier methods were used to determine overall survival (OS) and progression-free survival (PFS). Results: The median age at diagnosis was 43 years (16-69 years), and 62% were females. FLT3-ITD and NPM1 mutations were found for 17.8% and 13.3% of patients, respectively. 85% of the patients had a normal karyotype. For efficacy, 52% of patients were eligible for the next treatment after complete remission. Refractory patients were 20%. Early mortality was 28.8%. Median values of PFS and OS were 3.6 and 8.2 months, respectively. Patients presenting FLT3 mutation and stem cell transplantation had PFS and OS of 20 and 43 months, respectively. Conclusion: The outcomes were consistent with the literature. Waiting time was not critical for treatment outcomes.